National Early Warning Score Parameters at the Emergency Department as In Hospital Cardiac Arrest Predictors - Samsul Maarif; Teguh Wahju Sardjono; Yuliani Wiji Utami (GoAcademica Research & Publishing, 2020)
In Hospital Cardiac Arrest (IHCA) is fairly common occurrence, although it can be prevented. Physiological status monitoring at Emergency Departement (ED) is crucial for early detection of potential IHCA incidence. National Early Warning Score (NEWS) is a scoring system to assess deterioration of patient's condition, but it is not yet known which parameters that have predictive value for IHCA incidence. Examine NEWS parameters of the patients while at the ED that have predictive value of IHCA incidence. This study was conducted retrospectively on inpatient medical records. The NEWS parameters examined were respiration rate score, oxygen saturation score, body temperature score, systolic blood pressure score, pulse rate score and level of consciousness score. Logistic regression analysis was used to test the predictive ability of NEWS parameters. Total score NEWS proved to be correlated with IHCA incidence (p=0.000; r=0.434). Parameters that have predictive value are systolic blood pressure score (p=0.001; OR=14.730), respiration rate score (p=0.000; OR=14.483) and level of consciousness score (p=0.000; OR=6.920). The NEWS parameter when the patients will be transferred from ED to the wards that have predictive value for IHCA incidence are systolic blood pressure score, respiration rate score and level of consciousness score.